Effectiveness Of Health And Health Interventions For Anxiety And Emotional Well-Being In Breast Cancer: Review - Nurlela Petra Saragih; Elfrida Nainggolan; Ruth Sarah Julfrida Saragih; Dewi Sartika Munthe; Eka Isranil Laily; Maria Magdalena Saragi R; Almina Rospitaria Tarigan (International Journal of Health Engineering and Technology, 2026)
Breast cancer remains a critical global health burden as the most prevalent malignancy and a leading cause of female mortality, with profound physical, psychological, and economic consequences for patients and families. A comprehensive understanding of health-related quality of life (HRQoL) is essential, as over 50% of patients report significant anxiety and depression, which can worsen clinical prognosis and drastically reduce survival rates if left unmanaged. However, substantial research gaps persist, characterized by inconsistent findings regarding demographic variables influencing HRQoL and a limited synthesis of literature integrating ecological coping models and socio-relational self-efficacy across diverse cultural contexts. This systematic literature review aims to analyze the relationship between various coping resources and patients' psychological distress and quality of life during treatment and recovery. Adhering to the PRISMA protocol, this study systematically screened 473 articles from the Scopus database within the subject areas of nursing and psychology published through 2024. Furthermore, digital health (eHealth/mHealth) interventions, such as the "Yun Dong Ru Kang" rehabilitation app and text messaging programs. Consequently, a shift toward a holistic care model incorporating routine distress screening and work integration support is warranted. Practitioners should optimize digital technology for remote monitoring and strengthen social support to mitigate emotional vulnerability.